Assessment of Precast Concrete Deterioration in Marine Environments Using Non-Destructive Methods - Tarek Ibrahim Selouma; Walid Fouad Edris; Abd Al-Kader A. Al Sayed; Rashid Al-Marri; Mostafa Shaaban (Buildings)
Concrete structures in marine environments face significant degradation due to reinforcement corrosion caused by chloride ingress and sulfate attack. Poor construction quality, inadequate standards, and suboptimal design can further accelerate deterioration. Non-destructive testing (NDT) has proven valuable for durability assessment, yet its application remains limited due to the complex microstructural characteristics of concrete. This study establishes a comprehensive procedure for evaluating precast concrete degradation in marine environments using multiple characterization techniques. Two precast concrete elements with different cement types, CEM II A-L 42.5R and CEM I 42.5 R/SR, were analyzed through compressive strength tests, open porosity measurements, mercury intrusion porosimetry (MIP), ultrasonic wave transmission, and scanning electron microscopy (SEM). The results indicate that CEM I 42.5 R/SR exhibits superior compressive strength and lower porosity, making it more durable and suitable for load-bearing applications. Higher ultrasonic pulse velocity (UPV) further confirms its resilience. In contrast, CEM II A-L 42.5R shows lower mechanical performance and greater susceptibility to marine-induced degradation. Over time, pore size distribution shifts, potentially compromising mechanical integrity. SEM analysis reveals gypsum and brucite formation in degraded regions, demonstrating microstructural changes due to seawater exposure. A strong negative correlation between porosity and UPV underscores the detrimental effect of increased porosity on material density and structural stability. This study highlights the effectiveness of UPV and porosity analysis as reliable NDT techniques for assessing concrete deterioration. The strong correlation between UPV and porosity trends suggests that UPV serves as an early indicator of durability loss, enabling timely maintenance interventions. These findings provide valuable insights into material selection for enhanced structural performance in marine environments and emphasize the role of NDT in long-term structural health monitoring.